Synthesis and degradation of dinoflagellate plastid-encoded psbA proteins are light-regulated, not circadian-regulated - Wang, Yunling (National Academy of Sciences, 2005)
In many dinoflagellate species, the plastid genome has been proposed to exist as a limited number of single-gene minicircles, and many genes normally found in the plastid genome are nuclear-encoded. Unlike the nuclear-encoded plastid-directed gene products whose expression is often regulated by the circadian clock, little is known about expression of minicircle genes. Furthermore, even the plastid location of the minicircles has recently been challenged. We have examined the incorporation in vivo of [(35)S]methionine into the proteins of purified plastids, and we find that several plastid proteins are labeled in the presence of cycloheximide but not chloramphenicol. One of these proteins, labeled in two different dinoflagellate species, was identified as psbA by Western blot analysis. Furthermore, this psbA has the expected physiological characteristics, because both synthesis and degradation are induced by light. We find no evidence for circadian control over either synthesis or degradation of psbA, unlike the several nuclear-encoded plastid-directed proteins studied. Finally, we find that levels of psbA protein or RNA do not change over a 24-h light-dark cycle, suggesting that this protein may not be involved in mediating the circadian rhythm in oxygen evolution rates. This demonstration is the first, to our knowledge, that minicircle genes encoding plastid proteins are translated in dinoflagellate plastids, and it suggests that a proteomic approach to characterizing the dinoflagellate plastid genome is feasible.